Reinforcer magnitude and resistance to disruption of forgetting functions and response rates. Issue 3 (11th April 2014) - Berry, Meredith S.; Odum, Amy L.
Abstract The present experiment investigated the effects of reinforcer magnitude on resistance to disruption of remembering and response rates. Pigeons were exposed to a variable‐interval (VI), delayed‐matching‐to‐sample (DMTS) procedure with two components (rich and lean, distinguished by differing discriminative stimuli and hopper presentation duration). Completion of a VI 20 s schedule resulted in DMTS trials. In a DMTS trial, a choice of one of two comparison stimuli resulted in food if the choice matched the color of the previously presented sample stimulus. Separable aspects of the forgetting functions (initial discrimination and rate of forgetting) were examined by determining accuracy across a range of delays. Response rates and accuracy were higher in the rich relative to the lean component during baseline, and were more persistent during disruptors (extinction and prefeeding). During DMTS trials, extinction decreased initial discrimination more in the lean than the rich component, but had no systematic effect on rate of forgetting. During prefeeding, the rate of forgetting increased more in the lean than the rich component, but initial discrimination was not systematically affected. These results show persistence of response rates and remembering are positively related to reinforcer magnitude. The type of disruptor also influences the way in which remembering is disrupted.